Feasibility and safety of laparoscopic nephrectomy in emphysematous pyelonephritic kidneys - Raghuveer Machiraju; Devashish Kaushal; Jamal Rizvi; Gopal R Tak; Mandavi Agarwal (Asian Journal of Medical Sciences, 2022)
Background: Emphysematous pyelonephritis (EPN) is a serious suppurative infection of renal and extrarenal tissues. Most of them end up in nephrectomy, either in an emergency setting or delayed, which is increasingly favored. Laparoscopic nephrectomy is difficult in the post-EPN state due to dense adhesion around the kidney. Aims and Objectives: In this study, we want to check the feasibility of laparoscopic nephrectomy in EPN kidneys. To the best of our knowledge, our series is the single largest series as of today with 10 cases of laparoscopic nephrectomies in EPN kidneys. Materials and Methods: All patients of EPN who underwent laparoscopic nephrectomy at Institute of Kidney Diseases and Research Centre, Ahmedabad, between December 2017 and October 2019 were taken as study subjects and retrospectively reviewed. Patients in whom conservative management was successful were excluded from the study. All patients were diverted initially, either ultrasound/computed tomography-guided percutaneous nephrostomy (PCN) insertion or double J stenting, with or without PCN along with antibiotics and supportive therapy. Delayed transperitoneal laparoscopic nephrectomies were performed for poorly functioning EPN kidneys in follow-up renal scans. Results: A total of 10 patients underwent nephrectomy in this period. The male-to-female ratio was 3:7. As per Huang and Tseng’s EPN classification, one patient had Class 2, four patients had Class 3a, and five patients had Class 3b EPN disease. Mean operative time was 192 min and mean blood loss was 206 ml. Two cases had intraoperative complications managed laparoscopically. No conversion to open nephrectomy or mortality was seen. The drain was placed for a mean period of 3.1 days. The mean hospital stay was 4.8 days. Conclusion: Laparoscopy is safe and feasible for nephrectomy in EPN kidneys. Experience with laparoscopy and operating on pyelonephritis cases is important to reduce complications and extend the advantages of laparoscopy in these groups of patients. An increase in class does not increase the degree of difficulty during laparoscopy.